La globalización de la educación: lo humano; lo social y sus posibilidades de futuro - Jesús Antonio Quiñones (Pontificia Universidad Católica del Perú, 2009)
At the swing of the global economy, political trends and events that occur in the historical development of societies, it is occurring environmental, economic and social development phenomena that affect all citizens of the world, which has been understood as globalization. Given the irreversibility as economic fact, it should alert the entire school community in which the human values and essence of being a person are the most important concepts develop within the consumer society. This essay, beyond a critique of the globalizing phenomenon, explores its possibilities for the future, determining whether the constructs education and globalization can be mutually beneficial and not mutually exclusive.